Finding forgeries: Different strokes. (Economist, 2004)
An article published in the week of November 22, 2004, in the Proceedings of the National Academy of Sciences by Hany Farid and his team at Dartmouth College in New Hampshire presents statistical techniques that strive to detect forgeries in the art world by examining art itself— the message, not the medium. Farid explains that his technique, called wavelet analysis, can be thought to focus on the nature of the artist's brushstroke to distinguish between genuine and forged paintings. Details are provided of the development of Farid's technique and its proven and possible applications.